Manufacturing the ‘News Value’: How Pan-Arab Satellite TV Journalism Participated in Shaping the Palestinian Split - AlAhmad, Hussein (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims at emphasizing the term ‘news value’, as one central concept in mediatised conflicts. It so aims at examining the role that pan-Arab satellite TV journalism (henceforth PASTV) might have played in shaping political processes while covering the Palestinian internal conflict (Palestinian split). The study explores the PASTV’s involvement in the conflict and how that was reflected in the conflict and its political trajectories. Methods: Considering the three major pan-Arab transnational Satellite TV (PASTV) channels; Al-Jazeera, Al-Arabiya, and Al-Mayadeen as case studies, the study draws on qualitative data generated through a non-probability, reputational snowball sample, of thirty semi-structured interviews with key Palestinian ‘insiders’ in the two sectors of news media and politics, for their insight on the issue of research and its interlaced dimensions. Results: Data analysis shows with evidence, how, in their sought to meet the interests of their financers of political powers, PASTV channels framed the news –in varied levels between them- to create/maximize the news value and attract public attention. PASTV aimed at creating public consonance with a local ally, also marketing fear from the ‘other’. While serving their financers, PASTV produced ‘instrumental journalism’, and participated in shaping Palestinian politics, and the perpetuation of conflict became a by-product. Conclusions: Considering the interventionist role that most PASTV channels played. It is recommended that PASTV journalism can play both an objective and constructive role, and foster reconciliation policy prescriptions.